2019
DOI: 10.1038/s41439-019-0064-8
|View full text |Cite
|
Sign up to set email alerts
|

Retinal structure in Leber’s congenital amaurosis caused by RPGRIP1 mutations

Abstract: This study aimed to evaluate retinal structure in the early stage of Leber’s congenital amaurosis (LCA) caused by RPGRIP1 mutations. Four patients from two families were included. Case 1 was a 13-year-old girl, cases 2 and 3 were 7-year-old monozygotic twin brothers of case 1, and case 4 was a 17-year-old boy. Comprehensive ophthalmic examinations were performed, including visual acuity measurements, perimetry, electroretinography (ERG), and optical coherence tomography (OCT). To identify potential pathogenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 28 publications
2
21
0
Order By: Relevance
“…Review of the natural history of the disease and ophthalmological data in individuals carrying deep intronic RPGRIP1 pathologic variants in homozygosity or compound heterozygosity presented with nystagmus, oculo-digital signs of Franceschetti, photophobia, hyperopia and a vision function from light perception to at best 10/200. This disease presentation is consistent with previous reports [ 19 , 20 , 21 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Review of the natural history of the disease and ophthalmological data in individuals carrying deep intronic RPGRIP1 pathologic variants in homozygosity or compound heterozygosity presented with nystagmus, oculo-digital signs of Franceschetti, photophobia, hyperopia and a vision function from light perception to at best 10/200. This disease presentation is consistent with previous reports [ 19 , 20 , 21 ].…”
Section: Resultssupporting
confidence: 93%
“…These include RPGRIP1 , a pathologic variant which has been reported to cause an early-onset cone–rod dystrophy with loss of vision in teenage (CORD13, MIM608194; [ 27 ]). Individuals carrying the c.1468-128T>G in homozygous or in heterozygous state with a loss-of-function variant or the other deep intronic c.930+77A>G change, displayed a typical RPGRIP1 -associated LCA disease [ 19 , 20 , 21 ]. This observation suggests that both the c.1468-128T>G and c.930+77A>G variants have a deleterious impact on photoreceptor connecting cilium where RPGRIP1 localises.…”
Section: Discussionmentioning
confidence: 99%
“…[75,78]. OCT images usually demonstrate a thinner ONL and disorganized EZ, especially parafoveal [78,79]. However, Miyamichi et al reported better retention of retinal structure on OCT before the age of 5 in their case series [78].…”
Section: Rpgrip1mentioning
confidence: 91%
“…OCT images usually demonstrate a thinner ONL and disorganized EZ, especially parafoveal [78,79]. However, Miyamichi et al reported better retention of retinal structure on OCT before the age of 5 in their case series [78]. In previous reports, despite the relative foveal sparing on OCT and fundus examination, cone response was generally diminished on ERG, but rod function remained detectable in some younger cases [77,78].…”
Section: Rpgrip1mentioning
confidence: 92%
See 1 more Smart Citation